Partisipasi Stakeholder Eksternal dalam Meningkatkan Mutu Pendidikan di Sekolah Dasar - Sulistyorini Sulistyorini (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2018)
Elementary schools are designed to provide students with foundations of intelligence, knowledge, personality, and life skills as well as to prepare them to pursue higher education. The involvement of society in school development in important since education is an inseparable part of the society . The articals in order to be self-supporting andcontinue to the next level of education. Social involvement indeveloping schools is a proper thing due to education is a part of the social life essence. The society is not only concerned in education, but also tried to improve quality in order to create social roles through participations in educationa inschool developmentl institution. This research used qualitative approach and to collect the data used deep interview, partisipant observation and documentation. The present research was conductedto investigate the role of the society in two islamic primary schools and islamic elementary school in Blitar Regency, each of which had different characteristics. The research focused on investigating (a) the role of external stakeholder in developing education, school committee, class associations,busness world and industry, ex study and other agency (b) the role of external stakeholder in developing school equipment, help power, thought and ingredients. (c) the role of the stakeholder eksternal in improving the quality of education, non academic through supervisor and evaluation.